THE INFLUENCE OF GADGETS ON THE SOCIAL INTERACTION ON EXPENSIVE SOCIAL INTERESTS FACULTY OF PSYCHOLOGY UIN RADEN FATAH PALEMBANG - Salma Putri Nadipa; Silfi, Iffah Silfi Ulinni'mah; Kurnia Sintia Dewi; Menti Susanti; Noval Gerian Ramadhan; Muhammad Bariklana Almaghrib; Clarissa Salsabilla Gunawan; Maharani; Merti Anisman (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
Technology is a thing we can not avoid. The advancement of this technology is very helpful to students to find and get science quickly and learn can be done anywhere and anytime with the help of sophisticated communication tools. But in addition to the benefits that user can have, there is a negative impact such as emergence of lazy to perform social interaction and causes the decrease of concentration power especially when learning that does not benefit students become depressed as well as separate from its social environment. The purpose of this study is to know the negative impact of the use of gadgets that affect social interaction on students of Psychology UIN Raden Fatah Palembang. The research method used is predictive correlation with questionnaires as research instruments. The results of this study show the negative impact of the use of gadgets experienced by students in the form of lazy, physical fatigue, addiction resulting in money spending to buy pulses, reduced learning concentrations and other shapuings. The highest negative impact is the lazy student social activity of 81.81% and reduced the power of student concentration that even reaches 100% of the total students of the gadget user given the questionnaire.